(untitled) (Revista Innova Educación, 2022)
The objective of this research was to carry out a diagnosis of the development of the distance education experience through the emergence of COVID-19, at the Universidad Autónoma de Santo Domingo (UASD), San Francisco de Macorís, Santiago and Puerto Plata campuses and at the La Vega Center. The methodology implemented corresponds to the quantitative, descriptive, bibliographic and field approach. Among the most important results, it can be mentioned that 62% of the students responded that they were only receiving distance teaching in some of the subjects selected in the 2020-1 semester, while 16% indicated that they were receiving teaching in all subjects. In conclusion, the university platform is not used due to the lack of knowledge that teachers and students have about its implementation. Among the recommendations is the creation and strengthening of technological units to support teaching and students at all campuses and centers.